Automatic verification of urban index compliance: A case study for Brazilian buildings - Villaschi, F. S. (2022)
Urban planning has become an essential tool for regulating the cities' growth, maintaining the local urban identity and providing a good quality of life for its inhabitants. In Brazil, the master plan is the primary policy instrument for urban development and expansion. It defines the common requirements that designers must follow when preparing building projects. Up to date, such projects are verified in project latter stages and eventually approved by the city halls, with a manual calculation and assessment process. This procedure creates both the need to assess project compliance earlier to avoid rework and changes, as well as to automate project verification compliance, to reduce human errors. With the emergence of new technologies and computational systems, such as Building Information Modelling (BIM), creates the opportunity for process automation, by providing the required data to support decision making, as well as to automate the calculation process both for designers and municipalities. Thus, this research aims to develop an assessment procedure which automates the compliance assessment of a set of urban requirements from Vila Velha, Brazil. A BIM model was developed in Autodesk Revit to prove the procedure functionality and Dynamo was used to automate data collection and the calculation of three different indexes from Vila Velha's building code. By providing a fast and reliable analysis, the research framework provides designers with a real-time decision support tool, which indicates building compliance in the project's early stages. It also provides municipalities with a calculation tool, which can be used to assess the compliance of submitted BIM models, sparing time and avoiding assessment errors. Overall, the procedure has the potential to support building project design, increase process efficiency and accelerate the verification of mandatory requirements. It also offers the possibility for replication by adapting the routine to the mandatory requirements of each location.